Financial Literacy and Investment Behaviour of IT Professional in India - Mahabub Basha Shaik; M. Kethan; T. Jaggaiah; Mohammed Khizerulla (PT FORMOSA CENDEKIA GLOBAL, 2022)
IT sector plays a vital role in its contribution towards India’s GDP Savings and investments are imperative for fast-tracking economic growth and taking India to greater heights. The Purpose of this research is to understand the saving and investment behaviour of the IT professionals. There are various dimensions of savings and investment behaviour such as features of investment planning, determinants of investment preferences, IT Professionals have different mindset when they decide about investing in a particular avenue and they want his saving to be invested in most secure and liquid way. Though, the decision varies for every separate depending upon their risk aptitude. Their investment objective also differs from financial stability to additional income and so on. This paper attempts to find out the factors accountable for increased investing activities among young professionals. The current has studied the investment behaviour of IT investors by using a structured survey and this study inspects Behavioural Factors influencing towards Investment p among IT Professionals.